The Illocutionary Acts Of Written Conversation In Eleventh Grade Senior High School Students’ Textbook : Modul Pengayaan Bahasa Dan Sastra Inggris Peminatan Semester 2 - Yafet Seftyan Nugroho (Jurnal Sosial Teknologi, 2021)
Background: Language is method of human communication. It is used as means to communicate with other people. Research purposes: to find out the types of illocutionary act in Textbook : Modul Pengayaan Bahasa dan Sastra Inggris Peminatan Semester 2,  to identify dominant kinds of illocutionary act in Textbook : Modul Pengayaan Bahasa dan Sastra Inggris Peminatan Semester 2. Research methods: This reseacrh was designed as descriptive qualitative research. The technique of data collecting there are 3 steps. First, the researcher researcher tries to identify the data or the dialogues from the written conversation which are related to the statements of the problems according textbook. Second, the researcher analyzed and classified the types of illocutionary act and the dominant kinds of illocutionary act. Third, the researcher identified the illocutionary act found in Textbook : Modul Pengayaan Bahasa dan Sastra Inggris Peminatan Semester 2 based on types of illocutionary acts. Research results: The total number of types of the data found were 292, there were 34 utterance of declaration, 92 utterances of representative, 48 utterances of expressive, 95 utterances of directives, and 26 utterances of commisive. The dominant type of illocutionary was found is directives with 95 utterences Conclusion: Those were declarative, representative, expressive, directive, and commisive. To be more specific, there are 40 utterances of declarative, 85 utterances of representative, 53 utterances of expressive, 87 utterances of directive, and 26 utterances of commisive.